A self-paced reading study of language processing and retention comparing guided induction and deductive instruction. Issue 2 (16th October 2020) - Malovrh, Paul A.; Lee, James F.; Doherty, Stephen; Nichols, Alecia
Abstract : The present study measured the effects of guided-inductive (GI) versus deductive computer-delivered instruction on the processing and retention of the Spanish true passive using a self-paced reading design. Fifty-four foreign language learners of Spanish participated in the study, which operationalised guided-inductive and deductive approaches using an adaptation of the PACE model and processing instruction (PI), respectively. Results revealed that each experimental group significantly improved after the pedagogical intervention, and that the GI group outperformed the PI group in terms of accuracy on an immediate post-test. Differences between the groups, however, were not durative; at the delayed post-test, each group performed the same. Additional analyses revealed that the GI group spent over twice as much time on task during instruction than the PI group, with no long-term advantages on processing, calling into question the pedagogical justification for implementing GI at a curricular level.